Microscopic analysis of structural evolution in the Pt-Hg region - Prassa, Vaia; Karakatsanis, Konstantinos (HNPS Advances in Nuclear Physics, 2022)
The phenomena of shape-phase transitions and shape coexistence in neutron deficient even-even Pt and Hg isotopes are investigated, using a five-dimensional collective Hamiltonian (5DCH) based on covariant density-functional theory. The triaxial deformation energy surfaces in Pt isotopes display a transition from prolate (188Pt) to triaxial or oblate (190-198Pt), and to near spherical (198Pt) shapes. The calculations suggest coexisting configurations in 190Hg, γ-soft potential energy surfaces in 192-198Hg and a more spherical structure in 200Hg. The corresponding 5DCH model calculations confirm the structural evolution in this region and suggest more increased collectivity than what can be deduced from the data.